Nurses' sense of organizational support, Self‐esteem and perceived professional benefits: A mediating model - Mingjing Wang; Limin Wang; Caihong Lu (Wiley, 2023)
Abstract Aim To explore the mediating role of self‐esteem in the relationship between perceived organizational support and professional benefits among Registered Nurses in China. Design This was an online, cross‐sectional study involving 1850 nurses from six hospitals in China. Methods Data were collected using a 4‐part questionnaire including a sociodemographic questionnaire, perceived organizational support scale, self‐esteem scale and brief nurses' perceived professional benefits questionnaire from September to November 2021. Structural equation modelling (SEM) was used to explore the associations among them. Results Perceived organizational support was positively correlated with self‐esteem and perceived professional benefits among nurses, whereas self‐esteem positively predicted nurses' perceived professional benefits . Self‐esteem partially mediated the relationship between the two variables. The ratio of the mediating effect to the total effect was 16.7%.